Bentuk Toleransi Antar Umat Beragama dalam Menjaga Identitas Nasional dan Bhineka Tunggal Ika - Fennyta Melasari; Mira Detasari; Febiola Sriwulan; Rycko Verliansyah; Lara Santi; Rolan Si Ariko; Okta Tri Reski (IJOCE: Indonesia Journal of Civic Education, 2021)
ABSTRACT The purpose of this research is to form tolerance between religious communities in maintaining national identity and Bhineka Tunggal Ika. This research method is based on studies from international journals, namely, Islam and the relationship between religions (insights for Da'i). The results show that difference and diversity is a gift in human life. Differences arise from various aspects, such as differences in ethnicity, race, nation, and religion. Indonesia itself is formed from various tribes, races, and religions, so it is not uncommon for disagreements to occur between one ethnic group and another, or between one religion and another. The driving factor for the implementation of the value of tolerance is the understanding of Bhineka Tunggal Ika and Pancasila. So the Indonesian national identity is the identity that makes up the nation, namely various ethnic groups, religions, Indonesian language, national culture, the archipelago and the ideology of Pancasila. The conclusion of the study is that the form of tolerance between religious communities can be analogous to the human finger which consists of five different fingers, but all of them have their own functions and purposes, so that if all of them are put together they will be able to carry out any heavy task. Keywords: Bhineka Tunggal Ika, National Identity, Tolerance